Awareness of the Indian population regarding COVID-19 pandemic: a questionnaire-based survey - Senniyappan, Malar Kodi; Chellappan, Xavier Belsiyal; Deol, Rupinder; Garadi, Shweta; Sankarapandian, Chandrakala (International Journal Of Community Medicine And Public Health, 2020)
Background: The quick and widespread of the COVID-19 virulent disease has become a significant cause of concern among the general public and likely to adapt to this situation. People’s adherence to control measures is affected by their knowledge of COVID-19. This study aims to assess the awareness of the Indian population regarding the COVID-19 pandemic. Methods: A cross-sectional web-based anonymous survey conducted through an online platform (Google form) among the Indian population. A structured questionnaire was prepared to collect data about 5 minutes required to complete the questionnaire, and a total of 351 responses were received. Descriptive (frequency, percentage, mean, standard deviation) and inferential (chi-square) statistics used to analyze the collected data. Results: A total of 351 respondents have participated in this survey from different states/union territories were included in the analysis. 68.9% were had an adequate level of awareness, and 19.9% of was had an inadequate level of awareness. 78.6% were answered that the virus spreads through touching, coughing, sneezing; also, 78.3% were had knowledge regarding symptoms of COVID-19. Level of awareness was not associated with age, gender and variables were shown association. Conclusions: There is a need to intensify the awareness of people during this COVID-19 pandemic.